Keragaan Produksi dan Organisme Pengganggu Tanaman Padi, Jagung, dan Kedelai di Provinsi Riau - Rustam, Rustam (Jurnal Agro Teknologi Tropika, 2016)
Production of food crops, especially rice, corn, and soybeans affected by plant pests. This study aims to analyze the performance of productions and pests of food crops in Riau province within the last 5 years. Secondary data including data on production and pest of food crops in the period 2011-2015 was obtained from the relevant institutions. To validation and complete the secondary data done excavation of primary data from someÂ  speakers who are competent. Data were analyzed descriptively, tabulatively and simply to answer the research objectives. The results showed that there has been a decline in production of food crops in Riau Province in the years 2011 - 2015 are quite high, namely rice from 524.788 tonnes to 403.917 tonnes (down 23.0%), corn from 33.197 tonnes to 30.870 tonnes (down 7.0% ), and soybeans from 7.100 tons to 2.145 tons (down 69.8%). The decrease in production primarily due to lower harvested area, with the percentage of each of them: rice 26%, maize 12%, and soybeans 76%. The production decline is also due to pest attack. The type and level of pest attack in the period 2011-2015 fluctuated. In rice plants, there are eight types of pest led to crop failure (puso), namely bird, rat, rice bug, golden apple snail, stem borer, brown spot disease, blast, and bacteria leaf blight then 9 pests cause heavy damage, namely mole cricket, black bug, wild pig, leaf folder, brown planthopper, armyworm, sheath blight disease, and iron toxicity. The total area of rice pest attacks by puso category 161,4 ha and heavily damaged 124,05 ha. In corn, there are three types of pest causing puso, namely wild pig, downy mildew, and armyworm then 5 pests cause heavy damage, namely cob borer, stem borer, leaf rust, leaf blight and brown spot. The total area of corn pest attack with puso category 7,06 ha and heavily damaged 14,5 ha. For soybean plants, no pests have caused puso and only one type of pest causing heavy damage, namely aphids, with area damaged only 0,07 ha.